1991
DOI: 10.1038/clpt.1991.108
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril effects on alcohol intake and other consummatory behaviors in alcoholics

Abstract: Animal studies suggest that angiotensin-converting enzyme inhibitors decrease alcohol intake. In a double-blind crossover study 42 normotensive alcoholics (36 men and six women) aged 24 to 65 years, consuming 8.2 +/- 2.3 (mean +/- SD) standard alcoholic drinks per day, were randomized to enalapril, 10 mg/day (n = 20) or 20 mg/day (n = 22), and placebo for 4 weeks. They monitored their daily alcohol intake and attended biweekly assessments, but no other treatment or advice was given. Compliance and alcohol inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The renin-angiotensin-aldosterone system seems to be involved in the regulation of alcohol consumption and tolerance, at least in rats (Grupp, 1991;Grupp et al, 1997;Naranjo et al, 1991;Spinosa et al, 1988). Aldosterone stimulates renal reabsorption of sodium and potassium excretion.…”
mentioning
confidence: 99%
“…The renin-angiotensin-aldosterone system seems to be involved in the regulation of alcohol consumption and tolerance, at least in rats (Grupp, 1991;Grupp et al, 1997;Naranjo et al, 1991;Spinosa et al, 1988). Aldosterone stimulates renal reabsorption of sodium and potassium excretion.…”
mentioning
confidence: 99%
“…Kraly and Jones (1999) also could not support the hypothesis that Ang II provides an inhibitory physiological control of ingestion of ethanol, and in fact demonstrated that losartan significantly inhibited alcohol intake in a two-bottle drink test. Finally, the work of Grupp and colleagues that hypothesized that Ang II reduced alcohol intake was tested in alcoholic humans and the results of that study were negative (Naranjo et al, 1991). These data may be reconciled by the hypothesis that only a prolonged increase in central Ang II and/or an upregulated central RAS is stimulatory to ethanol intake in rats.…”
Section: Discussionmentioning
confidence: 99%
“…El sistema renina-angiotensina central parece ser uno de los moduladores del consumo de alcohol 2 ; en efecto, estudios experimentales muestran que los inhibidores de la enzima convertidora de la angiotensina I en II, tales como el captopril 3 , enalapril 4 y el abutapril 5 disminuyen la ingestión de etanol y que la inyección directa de captopril en el órgano fornical de estos animales produce una reducción de su consumo 6 . Sin embargo, algunos trabajos clínicos comunican que estos fármacos no modifican el consumo de etanol en alcohólicos 7 .…”
Section: N V E S T I G a C I ó Nunclassified
“…Durante las dos primeras semanas, período basal sin tratamiento farmacológico y previa instrucción de una ficha de monitoreo a utilizar, los pacientes anotaron su ingestión diaria de bebidas alcohólicas la cual fue expresada como tragos alcohólicos estándar (TAS), correspondiendo 1 TAS a 13,6 g de etanol absoluto. Esta forma de automonitoreo retrospectivo es acertadamente confiable y ha sido validado previamente por otros estudios clínicos 7 . Los pacientes también midieron la intensidad de su craving por alcohol, es decir, su sensación de búsqueda compulsiva y sostenida por esta droga.…”
Section: Materials Y Métodounclassified